Pre-quake frequency characteristics of Ms ≥7.0 earthquakes in mainland China - Luo, Guofu; Ding, Fenghe; Ma, Heqing; Yang, Mingzhi (Frontiers in Earth Science, 2023)
In this study, natural orthogonal expansion was performed on earthquake frequencies to compute the pre-quake frequency fields of 9 Ms ≥7.0 earthquakes in mainland China from 1980 to 2020. The temporal and spatial pre-quake anomalies of these earthquakes were extracted from their frequency fields. We found that the majority of pre-quake temporal anomalies (i.e., variations exceeding two-times the absolute mean square error) of a strong earthquake are condensed within the first four frequency fields, and typically comprise multiple components. The temporal factor of the first frequency field usually accounts for the largest proportion of these anomalies (40%–60% of the entire field). Most Ms ≥7.0 earthquakes exhibited long-term anomalies 5–8 years before their occurrence; some presented medium-term anomalies 1–2 years prior to the quake, and only a few presented short-term and imminent anomalies (≤3 months before the quake). Anomalous seismic hazard zones have high-gradient turning points in regional frequency-field contour maps, and the epicenters of strong earthquakes are often located in areas containing active faults that have contour values. Through the comparison of seismic frequency field and the traditional method of regional seismic activity frequency (3 months), it is shown that the frequency-field time factor has the advantages of diversified and rich abnormal information. The slope comparison between the frequency field and the cumulative frequency curve shows that the frequency anomaly time of the two is consistent, and the conclusion is reliable. Therefore, the seismic frequency method can predict the occurrence time and location of strong earthquakes, which is closer to the predictable seismic model.